Penjadwalan Efektif dengan Metode Time Cost Trade Off (TCTO) pada Proyek Pembangunan Tangki Septik dan Sarana Pendukung - Ahlan Dai; Arfan Usman Sumaga; Mohamad Yusuf Tuloli (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This study presents an in-depth analysis of the impact of the Time-Cost Trade-Off (TCTO) method on the time and cost efficiency of a project for the construction of septic tanks and their supporting facilities in Boalemo Regency. This construction project is part of the implementation of a Presidential Instruction (Inpres) aimed at improving domestic wastewater management in the region, with the project carried out in five subdistricts: Paguyaman, Paguyaman Pantai, Wonosari, Botumoito, and Mananggu. The research methodology utilized relevant secondary data, including the Budget Plan (RAB), the predetermined project duration schedule, and technical implementation records from the field. These data were comprehensively analyzed using Microsoft Project software and manual calculations to identify the critical path, as well as to calculate the crash duration, crash cost, and cost slope. Several acceleration scenarios were tested by adding 2, 3, and 4 hours of overtime. The results indicate that the addition of 2 hours of overtime achieved the most efficient balance, shortening the project duration to 72 days with a total cost of IDR 12,570,663,957. Meanwhile, the 3-hour overtime scenario reduced the duration to 70 days at a cost of IDR 12,639,692,694, and the 4-hour overtime scenario cut the duration to 69 days with a cost of IDR 12,708,721,431. These findings demonstrate that acceleration through overtime offers flexible options for project managers to achieve efficiency while considering the associated cost implications.